ELECTROPHYSICAL PROPERTIES OF BaNd2−xSmxIn2O7 WITH SLAB PEROVSKITE-LIKE STRUCTURE - Titov, Y.A.; Slobodyanik, M.S.; Kuzmin, R.N.; Chumak, V.V. (Reports of the National Academy of Sciences of Ukraine, 2024)
The electrophysical properties of ceramic samples of BaNd2−xSmxIn2O7 solid solutions (x = 0, 0.5, 1.0, 1.5, and 1.8) with a two-slab perovskite-like structure have been investigated by impedance spectroscopy. For modeling the impedance spectrum, the method of equivalent circuits represented by radio elements is used. It allows to isolate the properties of microcrystalline grains of ceramics, i. e. the substance under study, without the influence of intercrystalline and electrode effects. The dependences of the complex impedance Z(ν) of BaNd2−xSmxIn2O7 ceramics on the frequency (ν = 1 ÷ 107 Hz) of the probing sinusoidal electrical signal and temperature (300—800 K) have been established and analyzed. The temperature dependence of electrical conductivity constant current has been investigated, the activation energies of electrical conductivity of BaNd2−xSmxIn2O7 ceramic grains have been determined. The analysis of the composition-structure-properties relationship of BaNd2−xSmxIn2O7 showed a significant effect of the size and strain of the interblock space on the parameters of BaNd2−xSmxIn2O7 electrical conductivity.